Ecological Conditions of Agricultural Land Use in Transcarpathia - Taraczközi, Kamilla (Acta Agraria Debreceniensis, 2004)
The unbalanced anthropogenic effects for several decades resulted in significant technogen damages in the ecosystem of Ukraine. Excessive land development, including the use of slopes, effected the disintegration of the natural balance of lands – arable-lands, meadows, forests, and watershed areas – producing quite a negative effect on the landscape’s nature itself. It has to be stressed that according to other indexes, too, agricultural lands show a tendentious deterioration.Erosion, caused by water and wind, is one of the most influential factors in the degradation of agricultural soils and in the reduction of the productiveness of benefital lands. Nowadays the degree erosion became significant and it directly endangers the existence of the soil which is a principal chain-link of the agricultural cultivation as well as an irreplaceable element of the biosphere.The social and political changes in Ukraine’s life demand fundamental modernization in the land utilization both in ecological and in economical aspects. However, these aims can be realized only if, during the developments, we base on the up-to-date results of agronomics, and we do further research in the relations of agricultural land use and environmental protection. According to the latest theories, rational and environmental-safe agricultural production relates to the optimum correlation of the natural- and agricultural- ecosystems as well as to the reconstruction of agricultural areas built on the basis of environmental protection.